PENGARUH KUALITAS PRODUK HARGA WORD OF MOUTH DAN TRUST TERHADAP KEPUTUSAN PEMBELIAN (Studi Pada Pembelian Pakaian Online di Instagram) - B31111115, Desy Merry Kristyne Simorangkir (Jurnal Manajemen Update, 2016)
The world technology is currently experience progress rapidly every year. The perpetrator business is very using technology in doing the sale of her product online. Particular in Instagram many market sell the clothes online, do this because easier for marketer to sell their clothes and can be seen by society at large. This study aims to analyzed the influenc the quality of product, price, word of mouth and trust about the purchase decision on the online clothes in Instagram. The reasearch using method causal quantitative. The population in this study is the general public using Instagram in Pontianak and who ever make purchases clothes in Instagram at least twice. The research using purposive sampling, the sample in this study amounts to 85 people. Analysis technique used that is multiple regression alalysis using the program SPSS version 16.0. Analysis result data obtained showed that the quality of product, price and trust influential no significant about the purchase decision online clothes in Instagram. While word of mouth influential significant about the purchase decision clothes in Instagram, with the value of signifikansi of 0,000 and value R2 of 46,9%, the balance while of 53,1% is another factor is not scrutinized in this study. Keywords : the quality of product, price, word of mouth, trust, purchase decision.